Uncommon pathogen, common activity: Streptococcus pneumoniae conjunctivitis outbreak traced to a primary school field trip - Xiaojian Duan; Xiaobin Ren; Kai Song; Jiayun Wang; Yi Wang; Yuanming Zhang; Li Ren; Liangliang Huo; Jing Wang (Frontiers in Public Health, 2026)
Background In December 2025, an outbreak of acute conjunctivitis emerged at a primary school in Hangzhou, China, affecting 48 students and yielding an attack rate of 2. 16%. The outbreak is of particular significance as it was attributed to Streptococcus pneumoniae , a pathogen seldom implicated in large-scale conjunctivitis outbreaks among school-aged children. Methods An epidemiological investigation, a case-control study, and laboratory analyses—comprising multiplex real-time PCR and bacterial culture—were conducted to determine the etiological agent and the source of transmission. Results A significant association was established between the outbreak and a recent educational field trip (OR = 6.42, 95% CI: 3.53–11.68), suggesting that such organized group activities may represent an important transmission setting for bacterial conjunctivitis. Laboratory analyses confirmed the presence of S. pneumoniae in conjunctival swabs and environmental samples collected from the field trip venue. Moreover, students treated with combination antibiotic therapy had a significantly shorter mean return-to-school time compared with those receiving monotherapy or no treatment ( p < 0.01). However, as treatment allocation was not randomized, this association should be interpreted as an observational finding rather than evidence of causal effectiveness. Conclusion This investigation underscores the distinct transmission risks inherent to field trips and emphasizes the imperative of embedding comprehensive infection prevention and control measures into the foundational planning of such activities.